Influence of Worm-wheel Rotational Deflection on Meshing Performance of the Cylindrical Roller Enveloping Internal Engagement Worm Gear - Song Yuanhong; Deng Xingqiao; Jiang Yuanyuan (Jixie chuandong)
The cylindrical roller enveloping end-face internal engagement worm gear with the worm-wheel rotational deflection is a novel transmission that can achieve multi-load and different corner angular outputs. Analysis of the effect of the worm gear deflection angle on potential root-cutting and rotation of performance is important for understanding the device. The analysis of root-cutting and performance of rotation is carried out by using boundary curve equation and rotational formula. The study indicates that the worm-wheel rotational deflection angle that is equal or larger than 44° has occurred undercutting,and the performance of rotation is degraded with the increase in wheel rotational angle; at the same time,performance of rotation is degraded with the increase in the curvature of the contact line on the cylindrical roller. The study provides a reference for the selection of the worm-wheel rotational deflection of this new driving.